Nookie's daring rescue! : supersmart dog - Eason, Sarah; Salle, Ludovic, 1985- (Bearport Publishing, [, 2023)
"When Scott Swift adopted an Alaskan husky named Nookie, he was looking for a four-legged buddy to join him on outdoor adventures. Soon, Nookie would set out for adventures of his own-and save a hiker's life in the process! Explore the exciting true story of a supersmart animal in this graphic nonfiction adventure. Then, learn more about these clever canines and read other stories of dog masterminds!"--
Includes bibliographical references and index.
Ages 8-11
Grades 4-6
Keywords: Rescue dogs -- Anecdotes -- Juvenile literature; Rescue dogs -- Anecdotes -- Comic books, strips, etc